2016
DOI: 10.3892/mmr.2016.5608
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the association between miR-181b, Bcl-2 and LRIG1 in oral verrucous carcinoma

Abstract: Abnormal expression of microRNAs (miRNAs) is involved in the development of and anti-apoptotic effects in various types of human cancer. However, miRNA-mediated regulation of oral verrucous carcinoma (OVC) remains to be elucidated. The present study aimed to investigate the expression of miR-181b in OVC and oral squamous cell carcinoma (OSCC). The expression levels of miR-181b were determined using reverse transcription-quantitative polymerase chain reaction. The expression levels of B-cell lymphoma 2 (Bcl-2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
3
0
2
Order By: Relevance
“…Deng et al and Jairajpuri et al also observed similar expression pattern in group II and III; however, Thennevan et al suggested very limited expression in verrucous lesions. 12 17 Corresponding with the previous studies we concur that a proportional rise in the BCL2 expression from group I to III reflects its part in disease progression by increasing the survival rate of neoplastic cells and allowing clones of the neoplastic cells to proliferate and differentiate. In group IV, BCL2 immunoexpression was exaggerated and primarily confined to peripheral cells of the tumor islands similar to studies conducted by Juneja et al and Sudha and Hemavathy ( Fig.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Deng et al and Jairajpuri et al also observed similar expression pattern in group II and III; however, Thennevan et al suggested very limited expression in verrucous lesions. 12 17 Corresponding with the previous studies we concur that a proportional rise in the BCL2 expression from group I to III reflects its part in disease progression by increasing the survival rate of neoplastic cells and allowing clones of the neoplastic cells to proliferate and differentiate. In group IV, BCL2 immunoexpression was exaggerated and primarily confined to peripheral cells of the tumor islands similar to studies conducted by Juneja et al and Sudha and Hemavathy ( Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Several authors have illustrated overlapping pathways of EZH2 and BCL2 in certain lymphoid malignancies which have significant treatment implications. 17,18 In cholangiocarcinoma cells EZH2 inactivates p16 and p27 which further suppresses apoptosis. 29 However, no such pathways have been explored in oral lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tendo em vista as limitações observadas para classificação das displasias epiteliais, assim como, da displasia epitelial severa e o carcinoma espinocelular de lábio inferior, buscamos verificar neste trabalho a expressão dos miRNA-181b, miRNA-21, miRNA-31 e miRNA-345 nas queilites actínicas e nos carcinomas espinocelulares de lábio inferior. A seleção destes miRNAs foi realizada com base em estudos prévios de leucoplasia bucal, outra lesão potencialmente maligna, (CERVIGNE et al, 2009;YANG et al, 2011;XIAO et al, 2012;BRITO et al, 2014;MAIMAITI et al, 2015;ZHU et al, 2015;HUNG et al, 2016) foi verificado nas neoplasias malignas mais avançadas (CERVIGNE et al, 2009;YANG et al, 2011;YANG et al, 2013;BRITO et al, 2014;DENG et al, 2016 Nossos resultados da expressão do miRNA-21 confirmam estudos prévios, em carcinomas hepatocelulares (MENG et al, 2007) e em carcinomas espinocelulares de cabeça e pescoço (LI et al, 2009;LIU, X. et al, 2009;CHEN et al, 2013;HEDBACK et al, 2014;SUN et al, 2014), que descreveram uma associação entre a maior expressão de miRNA-21 com a progressão destas neoplasias malignas. Este aumento da expressão do miRNA-21 como descrito no presente estudo, foi igualmente reportado nas leucoplasias bucais (CERVIGNE et al, 2009, BRITO et al, 2014ZHU et al, 2014;HUNG et al, 2015) e nos carcinomas espinocelulares de boca (LI et al, 2009;SIOW et al, 2014;ZHOU et al, 2014;TROIANO et al, 2018) A análise do miRNA-345 em lesões potencialmente malignas de boca como as leucoplasias bucais, foram realizados em poucos estudos (CERVIGNE et al, 2009;BRITO et al, 2014), sendo descrito um aumento da expressão deste miRNA nestas lesões, o que contrasta com nossos resultados.…”
Section: Registro Dos Dados Clínicos E Microscópicosunclassified
“…Outro miRNA que vem sendo investigado nos processos neoplásicos, incluindo os carcinomas espinocelulares de boca, é o miRNA-31 (LIU, C. J. et al, 2010;LIU, C. J. et al, 2012;SIOW et al, 2014;YAN et al, 2017 Outro miRNA que apresentou particular interesse em estudos iniciais do desenvolvimento tumoral em boca é o miRNA-181b, membro da família de miRNA-181s (CERVIGNE et al, 2009;YANG, C. C. et al, 2011;DENG et al, 2016). A família do miRNA-p27Kipl e Bcl-2, sendo a regulação do miRNA-181 mediada pelo silenciamento de fatores de transcrição específicos nos diferentes tipos de cânceres (YANG, C. C. et al, 2011;BRITO, J.…”
Section: Introductionunclassified